Intestinal epithelial culture under an air‐liquid interface: a tool for studying human and mouse esophagi. Issue 7 (23rd March 2015) - Yokobori, T.; Suzuki, S.; Miyazaki, T.; Sohda, M.; Sakai, M.; Tanaka, N.; Ozawa, D.; Hara, K.; Honjo, H.; Altan, B.; Fukuchi, M.; Ishii, H.; et al.
Summary: This study investigated whether an intestinal epithelial culture method can be applied to mouse and human esophageal cultures. The esophagi harvested from 1‐day‐old mice and adult humans were maintained in collagen gels. A commercially available culture medium for human embryonic stem cells was used for the human esophageal culture. We discovered that the intestinal epithelial culture method can be successfully applied to both mouse and human esophageal cultures. The long‐term cultured esophageal organoids were rod‐like luminal structures lined with myofibroblasts. We discovered that regeneration of the esophageal mucosal surface can be almost completely achieved in vitro, and the advantage of this method is that organoid cultures may be generated using host‐derived fibroblasts as a niche. This method is a promising tool for mouse and human research in intestinal biology, carcinogenesis, and regenerative medicine.